Alternatives for implementing methods for finding agents in a Multi-Agent Systems - Tucat, Mariano (2006)
Interaction is an essential characteristic of Multi- Agent Systems (MASs). Agents that are part of a MAS usually interact by exchanging messages accord- ing to some conversation policy. Therefore, the ability to find other agents and exchange messages with them are features that need to be implemented in agents that are part of a MAS. Finding an agent means been aware of it existence and obtaining the information needed to send to it a message. There exists different alternatives of implementing the capability of finding other agents. In this work we will analyze the al- ternatives of implementing a discovery mechanism, a centralized Agent Name Server (ANS), a distributed ANS, or several ANSs.